The Impact of TED Youtube Channel to Improve Listening in English Learning Students of TBI IAIN Cirebon - Lidia Ratnaningsih; Septi Gumiandari (International Journal of Educational Qualitative Quantitative Research, 2022)
In this modern era, the YouTube application is one of the media to improve students' English listening learning, one of which is through the TED YouTube channel. It also applies to students at IAIN Cirebon. However, in the process, it is not known whether this media has a positive impact or not in improving students' English listening learning. The purpose of this study is to see the effect of learning media from the TED YouTube channel on English listening learning for IAIN Cirebon students. This research used the descriptive quantitative method. The author surveyed the 3rd semester TBI students of IAIN Cirebon using an online questionnaire. The findings show that the use of media from the TED YouTube channel has a good impact on improving the English listening skills of IAIN Cirebon students. These positive impacts include increasing English vocabulary, students' ability to identify topics, and motivating students to practice English listening skills. In addition, students consider using video media from the TED YouTube channel as a fun way to practice English listening skills.